Migration of hardware Aladdin e-Token to soft-token OpenVPN to increase the quality of service (QoS) / Hasrulnudin Ahmad - Ahmad, Hasrulnudin (2014)
Aladdin e-Token for MRSM e-Education has been implemented since 2009 to ensure all critical data are not misusing or hacked by the outsider. Major issues with the administrator of MRSM e-Education project needs to configure and install the token. Secondly, the Aladdin e-Token’s password requirement on administrator or site admin before the tunnel is up. Lastly Aladdin e-Token configuration is in reliance to only a specific server. Due to this challenge, it will affect the QoS of the system in term of down time, performance, consistent and delay of data transfer. Therefore the study made to identify weaknesses Aladdin e-Token then build Soft-token and assess the ability of the Soft-token approach. The method is based on the Small RSA (easy-rsa) OpenVPN and all information included in the Soft-token. Based on four tests conducted on these two approach, hence the Soft-token more reliable, consistent response time, independent and time to transfer data faster than the Aladdin e-Token. In conclusion, the Soft-token is appropriate to replace hardware Aladdin e-Token OpenVPN and increase the Quality of Service for MRSM e-Education system.